Yearbook of food and agricultural statistics. - Food and Agriculture Organization of the United Nations (Washington [s.n.)
Annual
For record of volumes in Library see Serials Check List.
Issued 1947- by the Food and Agriculture Organization of the United Nations.
Supersedes the International yearbook of agricultural statistics.
Keywords: Agriculture -- Statistics -- Periodicals